Enhancement on H+ carriers in conduction properties with addition of 1-butyl-3-Methylimidazolium chloride based alginate polymer electrolytes - A. F., Fuzlin; N. F., Mazuki; Hasan, Md. Mahmudul; Nagao, Y.; Ahmad Salihin, Samsudin (Elsevier Ltd, 2024)
A solution casting technique was used to fabricate a bio-based polymer electrolytes (BBPEs) system in the form of a solid film that is composed of alginate as the host polymer network, glycolic acid (GA) as the charge carrier, and 1-butyl-3-methylimidazolium chloride ([Bmim]Cl) ionic liquid (IL) as an additive. The peak changes in IR spectra revealed the complexation of adding ionic liquids with the enhancement of H+ carriers, while XRD and TGA studies revealed that adding IL suppressed the crystallinity and improved the thermal stability up to ∼100 °C. The free-standing BBPEs sample exhibited the highest ionic conductivity of 2.03 × 10−3 S cm−1 at 6 wt % [Bmim]Cl composition at ambient temperature and achieved an H+ transference number of 0.47. These results suggested that the addition of ILs as an additive into alginate-based BBPEs is a promising strategy for developing proton-conducting solid BBPEs for use in electrochemical devices.